Insertional inactivation of oprD in carbapenem-resistant Pseudomonas aeruginosa strains isolated from burn patients in Tehran, Iran. (January 2018) - Shariati, A.; Azimi, T.; Ardebili, A.; Chirani, A.S.; Bahramian, A.; Pormohammad, A.; Sadredinamin, M.; Erfanimanesh, S.; Bostanghadiri, N.; Shams, S.; Hashemi, A.
Abstract: In this study, we report the insertion sequence IS Ppu 21 in the opr D porin gene of carbapenem-resistant Pseudomonas aeruginosa isolates from burn patients in Tehran, Iran. Antibiotic susceptibility tests for P. aeruginosa isolates were determined. Production of metallo-β-lactamases (MBLs) and carbapenemase was evaluated and the β-lactamase-encoding and aminoglycoside-modifying enzyme genes were investigated by PCR and sequencing methods. The mRNA transcription level of oprD and mex efflux pump genes were evaluated by real-time PCR. The outer membrane protein proﬁle was determined by SDS–PAGE. The genetic relationship between the P. aeruginosa isolates was assessed by random amplified polymorphic DNA PCR. In all, 10.52% (10/95) of clinical isolates of P. aeruginosa harboured the IS Ppu 21 insertion element in the opr D gene. The extended-spectrum β-lactamase-encoding gene in IS Ppu 21-carrying isolates was bla TEM . PCR assays targeting MBL and carbapenemase-encoding genes were also negative in all ten isolates. The rmt A, aad A, aad B and arm A genes were positive in all IS Ppu 21 harbouring isolates. The relative expression levels of the mex X, mex B, mex T and mex D genes in ten isolates ranged from 0.1- to 1.4-fold, 1.1- to 3.68-fold, 0.3- to 8.22-fold and 1.7- to 35.17-fold, respectively. The relative expression levels of the oprD in ten isolates ranged from 0.57- to 35.01-fold, which was much higher than those in the control strain P. aeruginosa PAO1. Evaluation of the outer membrane protein by SDS–PAGE suggested that opr D was produced at very low levels by all isolates. Using random amplified polymorphic DNA PCR genotyping, eight of the ten isolates containing IS Ppu 21 were shown to be clonally related. The present study describes a novel molecular mechanism, IS Ppu 21 insertion of the opr D gene, associated with carbapenem resistance in clinical P. aeruginosa isolates.